2016
DOI: 10.7314/apjcp.2016.17.4.2235
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Spirogyra neglecta and a Polysaccharide Extract against Dextran Sodium Sulfate Induced Colitis in Mice

Abstract: Ulcerative colitis (UC) results from colonic epithelial barrier defects and impaired mucosal immune responses. In this study, we aimed to investigate the modifying effects of a Spirogyra neglecta extract (SNE), a polysaccharide extract (PE) and a chloroform fraction (CF) on dextran sodium sulfate (DSS)-induced colitis in mice and to determine the mechanisms. To induce colitis, ICR mice received 3% DSS in their drinking water for 7 days. Seven days preceding the DSS treatment, oral administration of SNE, PE and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
1
1
0
4
Order By: Relevance
“…In 2016, a study by Taya et al demonstrated that the extract (50 and 200 mg/kg) of Spirogyra neglecta, a freshwater green alga in the northern provinces of Thailand, diminished apoptosis of colonic epithelial cells in colitis mice via suppressing p38, ERK1/2, and MAP2K1 (Taya et al, 2016). Indirubin and Isatin are bioactive components in Qin Dai [Brassicaceae: Isatis tinctoria subsp.…”
Section: Extractsmentioning
confidence: 99%
“…In 2016, a study by Taya et al demonstrated that the extract (50 and 200 mg/kg) of Spirogyra neglecta, a freshwater green alga in the northern provinces of Thailand, diminished apoptosis of colonic epithelial cells in colitis mice via suppressing p38, ERK1/2, and MAP2K1 (Taya et al, 2016). Indirubin and Isatin are bioactive components in Qin Dai [Brassicaceae: Isatis tinctoria subsp.…”
Section: Extractsmentioning
confidence: 99%
“…berlimpah di habitat air tawar di seluruh dunia, dan terdiri dari sekitar 380 jenis (Takano et al, 2019). Mikroalga filamen air tawar (Spirogyra sp) menghasilkan metabolit sekunder seperti alkaloid, steroid, flavonoid, tanin dan terpenoid (Mesbahzadeh dkk., 2018), fenolat, glikosida, dan saponin (Taya et al, 2016). Sejumlah besar produk ganggang juga dapat menjadi bahan baku dalam industri makanan, kosmetik, biokimia dan farmasi.…”
Section: Abstrakunclassified
“…Pada 1 mL filtrat, ditambahkan 1 mL pereaksi Barfoed. (Farnsworth, 1966;Adusei et al, 2019) (Yoon et al, 2013;Taya et al, 2016;Takano et al, 2019 melarutkan pati, protein, klorofil, resin, dan minyak mudah menguap. Sel yang mengerut akan mengembang ketika direaksikan dengan kloralhidrat sehingga fragmen pengenal dapat terlihat jelas (Takano et al, 2019).…”
Section: Abstrakunclassified
See 2 more Smart Citations